Feasibility Of Screen Printing Carbon Electrode To Detect Ascorbic Acid - Bohiran, Muhammad Fahim Azim (Universiti Sains Malaysia, 2021)
Screen-printed carbon electrodes (SPCE) used for electrochemical detection consist of three electrodes: auxiliary, working, and reference electrode. The working electrode is the principal electrode on which electrochemical reactions are performed, while the reference and auxiliary electrodes are used to complete the electronic circuit. The effect of varying the working electrode conductive ink thickness (2, 3, 4, 5, and 7 layers of SPCE) on the final electrochemical activity was investigated in this study. The depth of SPCE been submerged in 20mL of analyte is fixed at 1.5 cm since the exact length is unknown. It shows that by increasing the layer of conductive ink thickness, the oxidation peak is increasing too. Four-layer SPCE gives the optimum results for detection of AA at a concentration of 3mM to 10mM with the R2 value is almost 0.99. Besides, this report also investigates the selection of ascorbic acid (AA) from citric acid (CA) by using the four-layer SPCE.